2023
DOI: 10.1136/bmjopen-2023-076118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise interventions on brain-derived neurotrophic factor expression in people with overweight and obesity: protocol for a systematic review and meta-analysis

Wilson Kin Chung Leung,
Suk Yu Yau,
Lorna Kwai Ping Suen
et al.

Abstract: IntroductionEpidemic obesity (‘globobesity’) has led to a considerable rise in the prevalence and incidence of many disabling conditions, including cognitive dysfunction. Recent evidence has suggested that habitual exercise can alleviate the deleterious effects of obesity on cognitive functioning across the lifespan. Given that there is a potential link among obesity, exercise, cognitive health and brain-derived neurotrophic factor (BDNF), this systematic review aims to critically appraise interventional trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Lastly, we did not involve qualified librarians in the electronic database search. Given that the first author (Leung WKC) had previous experience of conceiving and conducting scoping or systematic review research [ 21 , 36 , 51 ], we believe that our search strategy for electronic databases was trustworthy and sensitive enough for comprehensive coverage of the available literature as exemplified by a retrieval of more than 800 records by our electronic database search and only 0.8% ( n = 7) included for review and reporting. Moreover, previous studies showed that electronic database search using PubMed and EMBASE covered up to 91% of the published literature [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we did not involve qualified librarians in the electronic database search. Given that the first author (Leung WKC) had previous experience of conceiving and conducting scoping or systematic review research [ 21 , 36 , 51 ], we believe that our search strategy for electronic databases was trustworthy and sensitive enough for comprehensive coverage of the available literature as exemplified by a retrieval of more than 800 records by our electronic database search and only 0.8% ( n = 7) included for review and reporting. Moreover, previous studies showed that electronic database search using PubMed and EMBASE covered up to 91% of the published literature [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%